ESGO/ESTRO/ESP Guidelines for the management of patients with cervical cancer - Update 2023 - Cibula, David; Raspollini, Maria Rosaria; Planchamp, François; Centeno, Carlos; Chargari, Cyrus; Felix, Ana; Fischerová, Daniela; Jahnn-Kuch, Daniela; Joly, Florence; Kohler, Christhardt; Lax, Sigurd; Lorusso, Domenica; et al. (International journal of gynecological cancer, 2023)
In 2018, the European Society of Gynecological Oncology (ESGO) jointly with the European Society for Radiotherapy and Oncology (ESTRO) and the European Society of Pathology (ESP) published evidence-based guidelines for the management of patients with cervical cancer. Given the large body of new evidence addressing the management of cervical cancer, the three sister societies jointly decided to update these evidence-based guidelines. The update includes new topics to provide comprehensive guidelines on all relevant issues of diagnosis and treatment in cervical cancer.To serve on the expert panel (27 experts across Europe) ESGO/ESTRO/ESP nominated practicing clinicians who are involved in managing patients with cervical cancer and have demonstrated leadership through their expertise in clinical care and research, national and international engagement, profile, and dedication to the topics addressed. To ensure the statements were evidence based, new data identified from a systematic search was reviewed and critically appraised. In the absence of any clear scientific evidence, judgment was based on the professional experience and consensus of the international development group. Before publication, the guidelines were reviewed by 155 independent international practitioners in cancer care delivery and patient representatives.These updated guidelines are comprehensive and cover staging, management, follow-up, long-term survivorship, quality of life and palliative care. Management includes fertility sparing treatment, early and locally advanced cervical cancer, invasive cervical cancer diagnosed on a simple hysterectomy specimen, cervical cancer in pregnancy, rare tumors, recurrent and metastatic diseases. The management algorithms and the principles of radiotherapy and pathological evaluation are also defined.
Keywords: Uterine Cervical Neoplasms; Female; těhotenství; Radiation Oncology; radiační onkologie; nádory děložního čípku; Pregnancy; ženské pohlaví; Humans; lidé; Europe; Evropa; lékařská onkologie; kvalita života; Quality of Life; Medical Oncology